New times and new texts : reconceptualising literacy education for the twenty-first century / Moses Samuel and Saratha Sithamparam - Samuel, Moses; Sithamparam, Saratha (Academy of Language Studies & UPENA, 2005)
This article offers a framework for reconceptualising literacy education in the context of globalisation and technological developments that have impacted the nature of texts and literacy practices. It examines the changing notions of literacy outlining the emergence of new text forms and literacy practices in the postindustrial era of new times. This sets the stage for a discussion of the implications for literacy education in the twenty-first century. The article argues for a rethinking of the goals of literacy education as well as pedagogical approaches and the kinds of texts that need to feature if school is to the prepare the learner for real world literacy practices.